Trusted evidences on the digital transformation of classic cars restoration - Murta, J.; Amaral, V.; Brito e Abreu, F. (Procedia Computer Science, 2024)
Classic automobiles are a crucial component of the automotive industry, representing specific eras’ historical, and technological accomplishments. However, to be regarded as masterpieces, these must be conserved in mint condition or restored following strict guidelines applied by expert services. Therefore, all data about restoration processes, and other relevant information about these vehicles, must be rigorously documented to guarantee its auditability and immutability. This paper reports on our ongoing research to properly provide such features to the classic car ecosystem. We are developing a blockchain-based solution that facilitates the adequate recording of classic car information, restoration procedures applied, and all associated documentation by ensuring this data is immutable and trustworthy, while also promoting collaboration between interested entities. Our proposed solution aims to be advantageous for all automotive entities involved. Additionally, it will be feasible to assess the impact of our system and its key technology, blockchain, applied to this particular domain.